Effect of heat treatment on mechanical properties and microstructure of selective laser melting 316L stainless steel - Kamariah, M.S.I.N. (Institute of Physics Publishing, 2017)
Selective Laser Melting (SLM) has been one of the preferred Additive Manufacturing process to fabricate parts due to its merits in terms of design freedom, lower material waste and faster production when compare to the conventional manufacturing processes. However, due to the thermal gradient experienced during the process, the parts are exposed to the residual stress that leads to parts distortion. This work presents the effect of heat treatments on the micro-hardness of 316L stainless steel parts. In current study, SLM has been employed to fabricate 316L stainless steel compacts. Different heat treatments of 650°C, 950°C, and 1100°C for 2 hours were applied on the compacts. Hardness test were performed on the as-built and heat-treated compacts. The relationship between the microstructures and micro-hardness were discussed in this paper. The results revealed that the micro-hardness of the as-built compacts is between 209.0 and 212.2 HV, which is much higher than the heattreated compacts. © 2017 Published under licence by IOP Publishing Ltd.